2020
DOI: 10.3389/fcell.2020.00377
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Infrared Spectral Histology of Skin Tissue Part II: Impact of a Lumican-Derived Peptide on Melanoma Growth

Abstract: Melanoma is the most aggressive type of cutaneous malignancies. In addition to its role as a regulator of extracellular matrix (ECM) integrity, lumican, a small leucine-rich proteoglycan, also exhibits anti-tumor properties in melanoma. This work focuses on the use of infrared spectral imaging (IRSI) and histopathology (IRSH) to study the effect of lumican-derived peptide (L9Mc) on B16F1 melanoma primary tumor growth. Female C57BL/6 mice were injected with B16F1 cells treated with L9Mc (n = 10) or its scramble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 67 publications
0
15
0
Order By: Relevance
“…Lumican (LUM) and Asporin (ASPN) belong to the small leucine-rich proteoglycan (SLRP) family consisting of a core protein with leucine-rich repeats and one or more attached glycosaminoglycan chains, which are considered to control the assembly of collagen fibers in the ECM. [23][24][25] LUM is an ECM localized proteoglycan associated with inflammatory conditions and known to bind collagens. 26,27 Previous study has indicated that LUM protein and mRNA levels are increased in cardiac tissues of patients and mice with HF compared with control hearts.…”
Section: Discussionmentioning
confidence: 99%
“…Lumican (LUM) and Asporin (ASPN) belong to the small leucine-rich proteoglycan (SLRP) family consisting of a core protein with leucine-rich repeats and one or more attached glycosaminoglycan chains, which are considered to control the assembly of collagen fibers in the ECM. [23][24][25] LUM is an ECM localized proteoglycan associated with inflammatory conditions and known to bind collagens. 26,27 Previous study has indicated that LUM protein and mRNA levels are increased in cardiac tissues of patients and mice with HF compared with control hearts.…”
Section: Discussionmentioning
confidence: 99%
“…Lumican (LUM) and Asporin (ASPN) belong to the small leucine-rich proteoglycans (SLRP) family consisting of a core protein with leucine-rich repeats and one or more attached glycosaminoglycan chains, which are considered to control the assembly of collagen bers in the ECM (23)(24)(25). LUM is an ECM localized proteoglycan associated with in ammatory conditions and known to bind collagens (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Jeanne et al identified lumican as an essential regulator of the tumor matrix structure and function [ 68 ]. Recently, in a mouse model of primary melanoma, the lumican-derived L9Mc peptide abrogated the growth and increased the apoptosis of B16F1 cells, as determined by infrared spectral imaging and histopathology [ 71 ].…”
Section: Lumican Structure Function and Expression-correlation With Carcinogenesismentioning
confidence: 99%
“…Thus, B16F1 cells transfected to overexpress lumican present an initiation and/or increase ofapoptosis [ 97 ]. Moreover, in a mouse model of B16F1 melanoma primary tumor growth, lumican treatment with the L9Mc peptide increased cancer cell apoptosis [ 71 ].…”
Section: Lumican At the Crossroad Between Apoptosis And Autophagymentioning
confidence: 99%